Coastal land subsidence accelerates timelines for future flood exposure in Hawai'i - Kyle Murray; Matthew Barbee; Philip Thompson; Charles Fletcher (Communications Earth & Environment)
Abstract Coastal subsidence exacerbates relative sea level rise, making low-lying areas vulnerable to flooding. In Hawai’i, the contribution of vertical land motion has not been fully studied. This is critical for urban O’ahu, where infrastructure is on low-lying coastal areas with varying sedimentary consolidation. Here we processed Interferometric Synthetic Aperture Radar data from 2006–2024 for the Hawaiian Islands, referencing them with Global Navigation Satellite System measurements to calculate subsidence rates. We also created a two-meter resolution digital elevation model for coastal O’ahu using 2007–2013 Federal Light Detection and Ranging data, which included hydro-enforcement and gap filling with reprocessed data. Using this elevation data and vertical land motion measurements, we numerically modeled flood exposure. Results suggest that while island-wide subsidence on O’ahu is about 0.6 ± 0.6 m m/y r, the south shore has localized rates exceeding 25.0 ± 1.0 m m/y r. This subsidence, which is much faster than Hawaii’s long-term sea level rise rate (1.54 mm/yr since 1905), could expand flood exposure by up to 53% by 2050 in the Mapunapuna industrial region. Accounting for subsidence compresses the timeline for flood preparedness by up to 50 years, emphasizing the need to integrate these insights into planning and policy for sustainable development and flood mitigation.